Pengaruh User Interface, Brand Image, dan Digital Literacy terhadap Minat Penggunaan Bank Digital - Muchammad Ghozi Izzuddin; Inayah Ilahiyyah (Jurnal Maksipreneur, 2022)
Changes always follow technological transformation in the pattern of community needs, and digital financial services are no exception. One of the alternatives that offer convenience and convenience in making transactions is gadgets, which are increasing in intensity in their use in the banking sector. This study aims to determine the effect of the independent variables, namely the user interface, brand image, and digital literacy, on the dependent variable, namely the interest in using digital banks. The research method used in this study is a quantitative method with an associative approach with a target of 120 respondents from the Y and Z generation groups. In contrast, the data analysis technique uses multiple linear regression analysis. The findings in this study indicate that the user interface and digital literacy variables have a partially significant effect on the interest in using digital banks. On the other hand, the brand image variable has no significant impact on the good of using digital banks. Simultaneously, the three variables consisting of the user interface, brand image, and digital literacy significantly affect the interest in using digital banks in generations Y and Z.